AB0614 A Comphehensive Analysis of 12 Disease-Specific Autoantibodies in Greek Patients with Systemic Sclerosis. (15th July 2016) - Liaskos, C.; Marou, E.; Simopoulou, T.; Barmakoudi, M.; Scheper, T.; Meyer, W.; Katsiari, C.G.; Bogdanos, D.; Sakkas, L.I.
Abstract : Background: Patients with systemic sclerosis (SSc) are characterized by ANAs against various autoantigens, none of which is 100% sensitive for the disease. The need for profiling testing based on a combination of the most important SSc-related autoantigens has led to the development of commercial SSc-profile assays. Objectives: To determine the diagnostic and clinical relevance of systemic sclerosis (SSc)-related autoantibodies tested by a line SSc-profile assay in a well defined cohort of Caucasian SSc patients, all from Central Greece. Methods: 98 consecutive patients with SSc (80 female, 18 male, mean age 57, 9±14, 9 y) including 60 patients with diffuse cutaneous SSc (dcSSc) and 38 with limited cutaneous SSc (lcSSc) were analyzed by a profile SSc line assay (Euroimmun) for autoantibodies against 12 autoantigens: Scl-70, Centromere (A, B), RNA polymerase III (subunits 11 & 155), fibrillarin, NOR90, Th/To, PM/Scl 100, PM/Scl75, Ku and PDGFR. Results: ANA by indirect immunofluorescence was present in 98 (98%) patients with SSc. Overall, 81 (82.6%) patients had abs against at least one of the 12 autoantigens. Anti-Scl-70 abs were present in 49 (49.4%) SSc patients, anti-centromere A in 22 (22.5%), anti-centromere B in 22 (22.5%, all anti-centromere A positive) anti-RNA polymerase III RP155) in 18 (18.3%) anti-RNA polymerase III RP11 in 14 (14.3%), anti-fibrillarin in 3 (3.1%), anti-Ku in 5 (5.1%), anti-NOR90 in 7 (7.1%), anti-PM/Scl100 in 4 (4.1%), anti-PM/Scl75 in 7 (7.1%), anti-Th/To in 4 (4.1%) and anti-PGDFR in 1 (1%) SSc patients. Overall, the most frequent anti-Scl-70, anti-centromere or anti-RNA polymerase III abs were present in 81 (81%) SSc patients while 6 (6.1%) lacked those antibodies and were positive for at least one of the other 9. Anti-Scl-70 were associated with diffuse SSc and ACA with limited SSc (p<0.001 for both). Positivity of Scl-70 was also correlated with the presence of lung fibrosis (p=0.004) and tended to be associated with the presence of digital ulcers (p=0.073). Anti-centromere abs were less prevalent in SSc patients with lung fibrosis (p=0.004). Anti-PM/Scl75 abs tended to be associated with the presence of digital ulcers (p=0.055). Anti-NOR90 abs were more frequent in male SSc patients (p=0.019). Conclusions: Anti-Scl70, anti-centromere and anti-RNA polymerase are by far the most dominant autoantibodies in SSc but other disease-related autoantibodies can also be present in SSc patients lacking those three autoantibodies. The presence of anti-Scl-70 abs identifies patients with lung fibrosis and along with anti-PM/Scl75 tend to be associated with the presence of digital ulcers. Disclosure of Interest: C. Liaskos: None declared, E. Marou: None declared, T. Simopoulou: None declared, M. Barmakoudi: None declared, T. Scheper Employee of: Euroimmun AG, W. Meyer Employee of: Euroimmun AG, C. Katsiari: None declared, D. Bogdanos: None declared, L. Sakkas: None declared